2001
DOI: 10.1007/s004280100444
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced in situ expression of aldose reductase in peripheral nerve and renal glomeruli in diabetic patients

Abstract: To explore the relationships between polyol pathway-related enzymes and pathologic features, we examined the immunohistochemical expression of aldose reductase (AR) and sorbitol dehydrogenase (SDH) in the peripheral nerve and kidney tissues collected postmortem from diabetic patients and compared it with those from non-diabetic patients. Tissue AR protein concentrations were also quantified. In non-diabetic patients, AR distributed in pericytes, smooth muscle cells of endo- and epi-neurial microvessels, Schwan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 43 publications
0
27
0
2
Order By: Relevance
“…AR is differentially expressed in mammalian kidney, where AR expression is low under physiological condition in the glomerulus but significantly increased in diabetic human patients (Corder et al, 1979; Kasajima et al, 2001). In diabetic rats, it was found that hyperglycemia-induced increase in glomerular sorbitol levels was attenuated by treatment with an AR inhibitor, sorbinil (Beyer-Mears et al, 1984).…”
Section: Aldose Reductase and Other Complications In Diabetesmentioning
confidence: 99%
“…AR is differentially expressed in mammalian kidney, where AR expression is low under physiological condition in the glomerulus but significantly increased in diabetic human patients (Corder et al, 1979; Kasajima et al, 2001). In diabetic rats, it was found that hyperglycemia-induced increase in glomerular sorbitol levels was attenuated by treatment with an AR inhibitor, sorbinil (Beyer-Mears et al, 1984).…”
Section: Aldose Reductase and Other Complications In Diabetesmentioning
confidence: 99%
“…The notion that NFAT5 is causally linked to these events is supported by the observation that AR is a prototypical NFAT5 target gene [66], and that NFAT5 shows increased DNA binding activity to its consensus sequence in PBMC from patients with diabetic microvascular complications compared with diabetic control subjects under hyperglycemic conditions [62]. Furthermore, enhanced expression of AR is observed in peripheral nerve and renal glomeruli in diabetic patients, and the degree of expression correlates with the disease score [67]. …”
Section: Pathologies Associated With Hyperosmolality and Inflammationmentioning
confidence: 99%
“…Nevertheless, detailed studies have revealed the presence of AR in mesangial cells (MCs) and in podocytes of the glomeruli [1416]. Increased expression of the enzyme has been demonstrated in the glomeruli of diabetic patients [17], while both mRNA and activity of AR were elevated in rat mesangial cells cultured in high glucose [18]. …”
Section: Introductionmentioning
confidence: 99%